AKIBAT HUKUM TERHADAP PERUSAHAAN YANG BELUM MENDAFTARKAN TENAGA KERJA WAKTU TERTENTU PADA PROGRAM JAMINAN SOSIAL KETENAGAKERJAAN DI PTPN IV KECAMATAN MELIAU - NIM. A1011201203, JAMES ANDRIAN SITUMEANG (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT LEGAL CONSEQUENCES FOR COMPANIES THAT HAVE NOT REGISTERED WORKERS FOR A CERTAIN TIME IN THE EMPLOYMENT SOCIAL SECURITY PROGRAM AT PTPN IV MELIAU DISTRICT The development of Indonesian industry has been aimed at improving the welfare of the community through the promotion of employment opportunities. This requires a comprehensive legal framework for employers and employees. Workers play an important role in increasing productivity and influencing the growth of the company. However, many Indonesian workers are not considered part of the BPJS program, raising concerns about health risks. The Program aims to provide social protection for all workers, including those who have worked above six months.The problem examined in the writing of this thesis is